Patience in the Perspective of Sufism: Spiritual Strategies for Students to Maintain Mental Health - Casmini Casmini; Pihasniwati Pihasniwati; Nuristighfari Masri Khaerani; Aurora Kholiev Nabila (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2025)
The high prevalence of mental health issues among university students highlights the need for a holistic treatment approach that includes not only medical and psychological care but also spiritual support. This study examines the concept of patience in Sufism as a practical spiritual strategy for coping with mental pressure. Using a qualitative phenomenological method, it explores the subjective experiences of eight students through in-depth interviews and focus group discussions. The findings indicate that students who practice patience through Sufi practices achieve enhanced emotional regulation, inner calmness, and spiritual resilience. Rather than mere endurance, patience functions as a spiritual framework that helps students reframe academic stress as divine tests, fostering steadfastness and a deeper sense of purpose. Contribution: This study contributes to the discourse on Islamic spirituality in psychology, offering an integrative, culturally rooted approach to student mental well-being. It also adds practical insight into applying Sufi teachings in modern contexts.